The First Step - Schriefer, Natalie (2023)
From a snowbank I watched the squirrel run.
Keywords: dept.hhs

Author, Edit Thyself. - Schriefer, Natalie (ASEE Prism, 2023)
The article focuses on providing tips to academics for improving the quality and acceptance chances of their scholarly work during the publishing process. Topics discussed include the benefits of reading work aloud to catch errors, batching tasks like reviewing reference lists and in-text citations, and the importance of carefully formatting tables and figures according to publication guidelines.
Keywords: Editing; Oral reading; Punctuation; Tense (Grammar); dept.hhs

Driving Directions - Schriefer, Natalie (Word Sports, 2023)
START: END: Trumbull High School Sacred Heart University 72 Strobel Road
Keywords: dept.hhs

Opinion: The new Zelda has finally arrived. It’s time for a rethink on video games. - Schriefer, Natalie (CNN, 2023)
I was thrilled when Nintendo released “The Legend of Zelda: Tears of the Kingdom” in May. But the unfettered joy I feel playing Zelda today took me longer to acquire than all 900 Korok seeds. While my parents supported my playing video games growing up, so many others blamed them for ruining lives, writes Natalie Schriefer.
Keywords: dept.hhs

How A Book From 1985 Unexpectedly Changed My View On My Sexuality - Schriefer, Natalie (HuffPost, 2023)
“I expected a lot of things when I started the novel … but I didn’t think it would feel culturally relevant in 2023.”
Keywords: dept.hhs

Funny Women: Query Letter for My Totally Publishable Novel - Schriefer, Natalie (The Rumpus, 2023)
(The previous sentence demonstrates both my market awareness and my forward thinking.)
Keywords: dept.hhs

Video Games and Resilience: Science Explains Why Playing Zelda Is Good For Your Brain - Schriefer, Natalie (Inverse, 2023)
Available to players of any skill level — no Twitch subscribers required.
Keywords: dept.hhs

Nintendo Has a Silent Problem With ‘Zelda’ Film - Schriefer, Natalie; CNN, sexuality She has written for; Think, NBC News; Insider; HuffPost; others. (Bloomberg.com, 2023)
A movie based on the popular video game will be inherently difficult because its recurring protagonist doesn’t speak. And developers have long preferred to keep it that way.
Keywords: Culture; Design; Generic 1st 'SI' Future; MAMMA MIA; MICROSOFT CORP; Markets; NETFLIX INC; NINTENDO CO LTD; Video Games; Women; dept.hhs; view